Microhardness and surface roughness of resin infiltrated bleached enamel surface using atomic force microscopy: An in vitro study - Alaa M. Alsafi; Nadia M. Taher (Saudi Dental Journal)
Aim: to evaluate the microhardness (VHN) and surface roughness (Ra) of human enamel surface treated with resin infiltration followed by in office bleaching and to study the effect of artificial saliva (AS) storage time on the VHN and Ra of resin infiltrated enamel. Materials and methods: Eighty enamel specimens were prepared from extracted human premolar teeth. Specimens were divided into two main groups (I and II) then, they were demineralized to create white spot lesions (WSLs). Group I was divided into A and B sub groups. Group A was treated with in office bleaching material while for group B, resin infiltration (Icon) was applied after 24 h storage in AS followed by bleaching. Group II was divided into (C and D). Group C was treated like group B. Specimens in group D were stored in AS for 14 d after treatment with Icon and before application of bleaching. Atomic force microscopy (AFM) Ra analysis and VHN calculation were done. Independent T Test was used to compare between groups at P < 0.05. Results: Group B demonstrated a significant increase in VHN compared with group A. Storage time in AS showed no significant difference on VHN or Ra between groups. Conclusion: Application of resin infiltration before bleaching significantly increased VHN and slightly improved Ra of WSLs compared with bleaching alone. Application of bleaching material after 24 h or 14 days of the application of resin infiltration did not have a significant effect or surface hardness or roughness of WSLs.